2019
DOI: 10.3847/1538-4357/ab4b47
|View full text |Cite
|
Sign up to set email alerts
|

NuSTAR and Chandra Observations of New X-Ray Transients in the Central Parsec of the Galaxy

Abstract: We report NuSTAR and Chandra observations of two X-ray transients, SWIFT J174540.7−290015 (T15) and SWIFT J174540.2−290037 (T37), which were discovered by the Neil Gehrels Swift Observatory in 2016 within r ∼ 1 pc of Sgr A*. NuSTAR detected bright X-ray outbursts from T15 and T37, likely in the soft and hard states, with 3-79 keV luminosities of 8 × 10 36 and 3 × 10 37 erg s −1 , respectively. No X-ray outbursts have previously been detected from the two transients and our Chandra ACIS analysis puts an upper l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 79 publications
2
7
0
Order By: Relevance
“…The present epoch is assumed to be typical, so ∼300 massive stars form every few million years, and become black holes and neutron stars. This model approximately reproduces the observed stellar density profile in the Galactic Center, as well as the recently discovered population of black hole X-ray binaries in the central parsec (Hailey et al 2018;Mori et al 2019) via tidal capture of main-sequence stars. This model implicitly assumes the IMF in the disk is truncated near 10M , which is problematic as the hypervelocity star observed by Koposov et al (2020) is an A-type star with a few solar masses.…”
Section: The Galactic Centersupporting
confidence: 74%
“…The present epoch is assumed to be typical, so ∼300 massive stars form every few million years, and become black holes and neutron stars. This model approximately reproduces the observed stellar density profile in the Galactic Center, as well as the recently discovered population of black hole X-ray binaries in the central parsec (Hailey et al 2018;Mori et al 2019) via tidal capture of main-sequence stars. This model implicitly assumes the IMF in the disk is truncated near 10M , which is problematic as the hypervelocity star observed by Koposov et al (2020) is an A-type star with a few solar masses.…”
Section: The Galactic Centersupporting
confidence: 74%
“…However, the reflionx hd model assumes an optically thick, slab-like atmosphere of a constant density (Ross & Fabian 2005). Thus, in our implementation, the X-rays are assumed to be reflected from a single layer at a single photoionization radius (R ion , Mori et al (2019)). Therefore, following Mori et al (2019), we perform a sanity check for the self-consistency of best-fit M4 model parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in our implementation, the X-rays are assumed to be reflected from a single layer at a single photoionization radius (R ion , Mori et al (2019)). Therefore, following Mori et al (2019), we perform a sanity check for the self-consistency of best-fit M4 model parameters. Assuming an isotropically emitting illuminating source (the corona), the ionisation parameter in reflionx hd model can be redefined as ξ = L nR 2 ion (where L is the illuminating luminosity, n is the hydrogen number density).…”
Section: Discussionmentioning
confidence: 99%
“…3) X-ray transients: Daily Swift/XRT monitoring since 2006, combined with other frequent X-ray observations of the GC, resulted in the detection of 20 X-ray transients in the central ∼50 pc (Muno et al, 2005;Degenaar et al, 2015). Six of the GC transients were identified as NS-LMXBs through the detection of type I X-ray bursts or pulsations (Degenaar et al, 2012), while NuSTAR observations identified two recent Swift transients as outbursting BH-LMXBs (Mori et al, 2019). Otherwise, ∼10 VFXTs have been detected with peak luminosities of L X ∼ 10 34 -10 36 erg s −1 (Degenaar et al, 2015) but their identity remains elusive despite extensive investigations by Swift-XRT (Degenaar et al, 2015).…”
Section: X-ray Source Population In the Gc And Bulgementioning
confidence: 99%
“…Frequent X-ray monitoring of the GC with Swift-XRT resulted in the detection of ∼20 Xray transients in the GC (Degenaar et al, 2015). Follow-up X-ray observations with Chandra, XMM-Newton and NuSTAR enabled the identification of some of those transients (Mori et al, 2013;Mori et al, 2019).…”
Section: Introductionmentioning
confidence: 99%